Application of RNA Interference Technology to Acroporid Juvenile Corals - Yuyama, Ikuko; Higuchi, Tomihiko; Hidaka, Michio (Frontiers in Marine Science, 2021)
Numerous genes involved in bone morphogenesis, algal endosymbiosis, skeletogenesis, and the stress response have been identified in corals by large-scale gene expression analysis, but functional analysis of those genes is lacking. There are few experimental examples of gene expression manipulation in corals, such as gene knockdown by RNA interference (RNAi). The purpose of this study is to establish an RNAi method for coral. As a first trial, the genes encoding green fluorescent protein (GFP, a fluorescent dye possessed by corals) and thioredoxin (TRX, a stress response gene) were selected for knockdown. Synthesized double-stranded RNAs (dsRNAs) corresponding to GFP and TRX were transformed into corals by lipofection method to attempt RNAi. Real-time PCR analysis to verify knockdown showed that GFP and TRX expression levels tended to decrease with each dsRNA treatment. In addition, stress exposure experiments following RNAi treatment revealed that corals with TRX knockdown exhibited increased mortality at elevated temperatures. In GFP-knockdown corals, decreased GFP fluorescence was observed. This study showed that lipofection RNAi can be applied to coral planula larvae and polyps after settlement, and that this method provides a useful tool to modify expression of genes involved in stress tolerance and fluorescence emission of the corals.